2008
DOI: 10.1007/s11172-008-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immobilization on the main dynamic characteristics of the enzymatic oxidation of methane to methanol by bacteria Methylosinus sporium B-2121

Abstract: The main dynamic characteristics of biochemical methanol formation by the oxidation of methane using a biocatalyst were studied. The biocatalyst is based on cells of bacteria Methylosinus sporium B 2121, both suspended in a medium and immobilized in the poly(vinyl alcohol) cryogel. The change in the methane concentration and the biocatalyst amount affects the productivity of the system, the maximal concentration of methanol in the cultural liquid, and the rate of methanol accumulation. The most part of the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Similar trends have been reported in M. sporium using raw biogas and synthetic gas mixture (CH [28]. In this study, methanol production was found to be significantly higher than reported in earlier studies on M. sporium B2121, where an increase in yield from 0.22 to 1.94 mM was obtained upon increasing the inoculum size from 35 to 105 mg of cells/ml [37,39]. In contrast, a lower inoculum of ) as a feed [43].…”
Section: Effect Of Inoculum Size On Methanol Productionsupporting
confidence: 86%
“…Similar trends have been reported in M. sporium using raw biogas and synthetic gas mixture (CH [28]. In this study, methanol production was found to be significantly higher than reported in earlier studies on M. sporium B2121, where an increase in yield from 0.22 to 1.94 mM was obtained upon increasing the inoculum size from 35 to 105 mg of cells/ml [37,39]. In contrast, a lower inoculum of ) as a feed [43].…”
Section: Effect Of Inoculum Size On Methanol Productionsupporting
confidence: 86%
“…Here, an increase in methanol production was observed from 3.87 to 5.13 mM by increasing cell biomass from 1.5 to 18 mg of DCM· mL -1 . In contrast, much higher cell inoculum (105 mg of DCM· mL -1 ) of M. sporium B21 resulted in significantly lower methanol production of 0.35 mM (Razumovsky et al, 2008). In addition, higher inoculums (12 and 18 mg of DCM· mL -1 ) of M. sporim resulted in faster methanol production, compared to lower inoculums (3 mg of DCM· mL -1 ) up to 32 h of incubation.…”
Section: Effect Of the Inoculum On Methanol Productionmentioning
confidence: 87%
“…Very few reports are available on methanol production by immobilized methanotrophs. The use of covalently immobilized M. trichosporium NCIB 11131 on DEAE-cellulose and encapsulated cells of M. sporium B-2121 in poly(vinyl alcohol) cryogel has been shown to enhance the stability of methanol production efficiency compared with the use of free cells [24,36]. In this study, the cell entrapment of M. tundrae in alginate beads was evaluated.…”
Section: Whole-cell Immobilization and Methanol Productionmentioning
confidence: 99%